Europian Union and dilemas unresolved balkan - Kastrati, Shqipe; Kastrati, Albana (Technium Education and Humanities, 2022)
The Europian Union is a “sui generis”organization(a special type),which one is evolving over the time.This organization is a conglomerate of nations which have a single goal,the progres of their country,in principle,always working through the advancement of the organization in general. Ways of organizing and the functioning of the EU, with some modifications, the weathered dignity,the challenge of growth.How ever,the changes can only move forward. Given this fact,we refer to the most important challenge of Europe and his Constitution.Ratification of the Treaty of Lisbon cut”troubled souls”in the EU since it is know that the treaty contained over 70% of the content of the Europian Constitutional Treaty.We can say that the Europian politics,this time has passed the test of challenging which was submitted to the mark the continuation of reforms in contradiction with their slowdown and stagnation. With the beginning of the democratic development in Easter Europe,the Albanians were the first who asked for their right to self-determination.For European recognition of the new republic crucial was status of a Republic and the combination of the principles of the concept of “European” and that “classic”. When there was not stability in Balkans,when the war in former Yugoslavia started in Slovenia,Croatia,Bosnia and Herzegovina,Kosovo was not independent,when the war began in the Presheva Valley,and in Macedonia,Kosovo was not independent. In a conclusion the answer to this wrong perception would be: the independence of Kosovo has stabilized the Balkans.